La psicomotricidad fina durante la educación virtual para el Nivel Inicial 2 en la Escuela de Educación Básica “Dr. Leónidas García Ortiz” ciudad de Riobamba, provincia de Chimborazo. - Apugllón Tenemasa, Jennyfer Alejandra (2023)
The present research with the theme "Fine psychomotor skills during virtual education for the preschool 2 children of the Basic Education School "Dr. Leónidas García Ortíz" city of Riobamba, province of Chimborazo. The objective of this study was: To analyze the fine psychomotor skills and the virtual education of children in the initial level 2 of the Basic Education School "Dr. Leónidas García Ortíz" city of Riobamba, province of Chimborazo. Its methodology was a mixed approach, with a non-experimental design, since there was no manipulation of variables, of transversal type, field study and bibliographic documentary, with a descriptive level, having a population of 30 research subjects comprised by the students of the initial level 2, to whom was applied the observation technique and as an instrument of data collection, an observation form. In this, the fine motor skills were worked on through the virtual education modality. It was determined that a high percentage of students do not have adequate manual coordination, do not achieve continuous strokes, do not have strength in wrists and fingers, among others, so that the methodological strategies used by the teacher are not adequate to provide classes in virtual mode. The conclusions reached after the results showed that the children do not have the activities and means to exercise the areas of fine motor development, which causes delays and unevenness when performing activities or exercises such as: continuous strokes, cutting paper, tearing, hand-eye coordination, hand strength, manual dexterities, etc. The application of activities with playful strategies, will allow students to work and improve fine motor movements, through better finger control, manual strength and improve school performance in general.